The Possibilities of Mri in the Establishment and Diagnosis of Lumbar Vertebral Stenosis - Toshtemirov O; Zulunov A.T; Ablyazov A.A (Zien Journals, 2023)
This article highlights the work devoted to the study of the possibility of MRI in the diagnosis of lumbar vertebral stenosis.
Keywords: tumor; MRI; stenosis